Participation engineer M.L. Schukin in the design and construction of the imperial train foreign and homeland track - Povisshaya, M. A. (History of science and technology, 2016)
The article highlights the participation of the outstanding Russian engineer of railways, designer of locomotives and wagons an extraordinary teacher and the railway administrator, Professor Nikolay Leonidovich Schukin in the design and construction of the imperial train foreign and homeland track. The result of work of the Construction Commission under the leadership of L. Schukin impressed. Effective cooperation leading railwaymen, scientists and engineers of country in the late XIX – early XX centuries has demonstrated a high level of engineering capability in the sector of railway transport and started the beginning of a new phase of homeland locomotive and wagons, little by littlededucing this industry on a par with the railways leading developed countries.